The acquisition and development of fitness trainers' professional knowledge - de Lyon, A. T. C.; Cushion, C. J. (The Journal of Strength and Conditioning Research, 2013)
This study investigated the acquisition and development of fitness trainers' knowledge and how this is related to their practice as health and exercise professionals. Semi-structured interviews were conducted with 11 fitness trainers, who had successfully completed a course accredited by a Register of Exercise Professionals (REPs) certifying organization. Findings were organized using Coombs and Ahmed's conceptual framework of formal, nonformal, and informal learning and later analyzed using Sfard's metaphors of learning. Results suggested that fitness trainers learn in multiple and complex ways, many of which are informal and arise through the naturalistic processes that occur within the context of their everyday work. The study concludes that there is a need for greater integration between the current formal (REPs) accreditation system and informal knowledge developed while working as a fitness trainer.